Complex interplay between determinants of pacing and performance during 20-km cycle time Trials - Renfree, A.; West, J.; Corbett, M.; Rhoden, C.; St Clair Gibson, A. (International Journal of Sports Physiology and Performance, 2012)
Purpose: This study examined the determinants of pacing strategy and performance during self-paced maximal exercise. Methods: Eight well-trained cyclists completed two 20-km time trials. Power output, rating of perceived exertion (RPE), positive and negative affect, and iEMG activity of the active musculature were recorded every 0.5 km, confidence in achieving preexercise goals was assessed every 5 km, and blood lactate and pH were measured postexercise. Differences in all parameters were assessed between fastest (FAST) and slowest (SLOW) trials performed. Results: Mean power output was significantly higher during the initial 90% of FAST, but not the final 10%, and blood lactate concentration was significantly higher and pH significantly lower following FAST. Mean iEMG activity was significantly higher throughout SLOW. Rating of perceived exertion was similar throughout both trials, but participants had significantly more positive affect and less nega- tive affect throughout FAST. Participants grew less confident in their ability to achieve their goals throughout SLOW. Conclusions: The results suggest that affect may be the primary psychological regulator of pacing strategy and that higher levels of positivity and lower levels of negativity may have been associated with a more aggressive strategy during FAST. Although the exact mechanisms through which affect acts to influence performance are unclear, it may determine the degree of physiological disruption that can be tolerated, or be reflective of peripheral physiological status in relation to the still to be completed exercise task.